Answer :

y = x^{2} + 5x + 4, x = –2, x = –3

When x = -2,

y = (-2)^{2} + 5×-2 + 4

= 4-10 + 4

= -2

When x = -3,

y = (-3)^{2} + 5×-3 + 4

= 9-15 + 4

= -2

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Quiz | Imp Qs. on Properties of Rational Numbers45 mins

Extra Questions on Laws of Rational Numbers40 mins

Missing Numbers55 mins

Properties of Rational Numbers29 mins

Essentials of Rational Numbers45 mins

On the Number line44 mins

Quiz | Properties of Rational Numbers41 mins

Squares of Numbers35 mins

Divisible or not41 mins

Quiz on Divisibility Test32 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation